A dual-mode sensor for colorimetric and "turn-on" fluorescent detection of ascorbic acid. (February 2018) - Liu, Yinghua; Wei, Zhenni; Duan, Wenxiu; Ren, Cuiling; Wu, Jiang; Liu, Dan; Chen, Hongli
Abstract: In the present work, a dual mode sensor, which was obtained by integrating B, N, S co -doped carbon dots and Fe 3+ (BNS-CDs@Fe 3+ ), was developed for sensing ascorbic acid (AA). The fluorescent signal of BNS-CDs@Fe 3+ sensor could be enhanced by AA, and a good linear relationship was obtained in the range of 0.1–600 μM with a detection limit down to 0.05 μM. More fascinatingly, the color of the sensor solution gradually changed from blue to red with the increasing concentrations of AA, which allowed establishing a simple colorimetric assay for AA detection in the linear range of 1–110 μM with a detection limit of 0.3 μM. Notably, a paper sensor for the determination of AA was developed with a lowest visual concentration of 1 μM, providing a novel and convenient platform for AA detection. More importantly, cell imaging experiments showed that this sensor can be applied for AA detection in HeLa cell, suggesting this sensing system holds great potential in biosensing and bioimaging. Highlights: A colorimetric and fluorescent dual mode sensor for AA was developed just by the ensemble of carbon dots and Fe 3+ . Fluorescent detection of AA can be realized by "turn-on" fashion. Test paper for determination of AA was developed based on colorimetric signal. This sensor can be successfully applied for intracellular imaging of AA.